The Abundance of the nifH Gene Became Higher and the nifH-Containing Diazotrophic Bacterial Communities Changed During Primary Succession in the Hailuogou Glacier Chronosequence, China - Wang, Yingyan; Chen, Yulan; Xue, Qinyu; Xiang, Quanju; Zhao, Ke; Yu, Xiumei; Chen, Qiang; Ma, Menggen; Jiang, Hao; Zhang, Xiaoping; Penttinen, Petri; Gu, Yunfu (Frontiers in Microbiology, 2021)
Primary successional ecosystems and the related soil development are often N limited. To date, N2-fixing communities during primary succession in alpine ecosystems have remained underexplored. In this study, we applied qPCR quantitation and targeted amplicon sequencing of nifH in Hailuogou Glacier foreland to investigate the succession of N2-fixing communities in five sites along a 62-year chronosequence. The abundance of nifH gene increased along the primary succession in the chronosequence and correlated positively with pH, acetylene reduction activity and water, organic C, total and available N and available P contents. The increases in alpha-diversity along the chronosequence may have been partly due to less competition for resources. In contrast to the clear separation based on soil properties, the changes in the diazotrophic community composition lacked a clear trend and were associated mostly with changes in soil available K and organic C contents. The changes among differentially abundant genera were possibly due to the changes in plant coverage and species composition. The whole primary succession of the diazotrophic communities was consistent with stochastic community assembly, which is indicative of low competitive pressure.